2017
DOI: 10.3310/hta21800
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for hyperhidrosis in secondary care: a systematic review and value-of-information analysis

Abstract: BackgroundHyperhidrosis is uncontrollable excessive sweating that occurs at rest, regardless of temperature. The symptoms of hyperhidrosis can significantly affect quality of life. The management of hyperhidrosis is uncertain and variable.ObjectiveTo establish the expected value of undertaking additional research to determine the most effective interventions for the management of refractory primary hyperhidrosis in secondary care.MethodsA systematic review and economic model, including a value-of-information (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 367 publications
(542 reference statements)
0
19
0
Order By: Relevance
“…To our knowledge, no prior cost-effectiveness evaluations have been published for first line treatments of PAHH. A previous evaluation of second line treatment sequences for refractory primary hyperhidrosis, but this analysis did not include first-line topical treatments [20] The treatment benefit of GT over prescription aluminum chloride is driven by both higher response rates for GT and higher persistence to GT than aluminum chloride. While some patients respond to prescription-strength aluminum chloride, tolerability may be hindered by skin irritation, which is a common adverse event [1,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no prior cost-effectiveness evaluations have been published for first line treatments of PAHH. A previous evaluation of second line treatment sequences for refractory primary hyperhidrosis, but this analysis did not include first-line topical treatments [20] The treatment benefit of GT over prescription aluminum chloride is driven by both higher response rates for GT and higher persistence to GT than aluminum chloride. While some patients respond to prescription-strength aluminum chloride, tolerability may be hindered by skin irritation, which is a common adverse event [1,43].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study is to estimate the cost-effectiveness of GT as a first-line topical therapy option for the treatment of PAHH compared to topical aluminum chloride from a United States payer perspective. the most commonly used tool to assess severity of disease and treatment effects over time [20]. The impact of hyperhidrosis and its associated symptoms is measured on a four-point scale which correspond to model health states: HDSS 1 (least severe, described as "sweating is never noticeable and never interferes with daily activities"), HDSS 2 ("My sweating is tolerable but sometimes interferes with my daily activities", HDSS 3 ("My sweating is barely tolerable and frequently interferes with my daily activities", and HDSS 4 (most severe, described as "sweating is intolerable and always interferes with daily activities") [21] .…”
Section: Introductionmentioning
confidence: 99%
“…The following databases were searched: MEDLINE, Embase, the Cochrane Database of Systematic Reviews (CDSR) and Cochrane Central of Controlled Trials (CENTRAL). Studies were identified 1) by reviewing and assessing those included in two related publications by Wade et al of the same search strategy and results [11,12] (RoB) in any review domains renders the overall study as at high or uncertain RoB [14]. Our assessment is that this standard is quite stringent and insufficiently contextual, which may result in the exclusion of results that are possibly reliable.…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
“…A systematic review first reported by Wade et al in 2017 [11] and subsequently in Wade et al 2018 [12] examined relevant evidence available in the scientific literature through July 2016 for primary hyperhidrosis treatments. However, several aspects of that analysis, including the lack of special consideration for those studies utilizing within-patient designs or with large response rates, the exclusion of aluminum/zirconium compounds commonly used for hyperhidrosis…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances being made in the treatment of hyperhidrosis over the last 100 years the availability of treatment options across the U.K. is not standardized. Current recommendations and practice are not based on strong clinical evidence . As we advance in an era of evidence‐based medicine with more involved patient choice, an in‐depth assessment of treatment studies is to be welcomed and this systematic review of hyperhidrosis is timely.…”
mentioning
confidence: 99%